A new tool for annotating scientific animations and supporting scientific dialogue. - Hui Liu; Margot Riggi; Jen Rogers; Miriah Meyer; Janet H Iwasa (PLoS Biology, 2022)
A new interactive annotation interface supports a detailed molecular animation of the SARS-CoV-2 life cycle. With this tool, users can interactively explore the data used to create the animation and engage in scientific discourse through comments and questions.